Development And In Vitro Characterization Of Hydrogel Containing A Combination Of Guduchi, Neem, And Calendula Extracts For The Treatment Of Diabetic Wound Healing (International Journal of Environmental Sciences, 2025)
Development And In Vitro Characterization of Hydrogel Containing a Combination of Guduchi, Neem, and Calendula Extracts for The Treatment of Diabetic Wound Healing. Managing chronic diabetic wounds is challenged by flawed angiogenesis, continuous infection, and oxidative stress. The use of herbal extracts with antimicrobial, antioxidant, and collagen-stimulating effects can be considered a possible substitution for standard wound therapies as it is safe and effective. The aim of the current study was to develop an in vitro characterization of a hydrogel containing a combination of Guduchi, Neem, and Calendula officinalis extract for the treatment of wound healing in Diabetes.To prepare the hydrogel containing the Guduchi, Neem, and Calendula officinalis extract. To characterize the various parameters of the hydrogel containing the Guduchi, Neem, and Calendula officinalis extract. To study the effect of the permeation enhancer on the drug release profile of extract extract-containing gel.A polyherbal hydrogel containing Tinospora cordifolia (Guduchi), Azadirachata indica (Neem), and calendula Officinalis, extracts was prepared and Carbopol 980 was the gel agent. UV and FTIR studies were done in preformulation to check compatibility. The pH, viscosity, spreadability, swelling index, water vapor transmission rate (WVTR), in-vitro drug release, and kinetics were determined on the hydrogel formulations.The physicochemical properties of the optimized hydrogel indicated desirable pH (6.2-6.8), good viscosity to be used as a topical, and consistency during spreading. No chemical incompatibilities were detected using FTIR. WVTR, as well as swelling index, confirmed proper moisture retention. In-vitro release data showed sustained release and was according to Higuchi kinetics. The polyherbal formulation offered synergistic wound-healing activity in terms of antimicrobial (Neem), antioxidant (Guduchi), and collagen-activating (Calendula) effects.